Trial results of the SYLOS few-cycle laser system of ELI-ALPS - Stanislauskas, T.; Budriunas, R.; Adamonis, J.; Aleknavičius, A.; Börzsönyi, A.; Tóth, Sz; Kovács, M.; Csontos, J.; Veitas, G.; Gadonas, D.; Masian, G.; Kuprionis, Z.; et al. (Proceedings of SPIE - The International Society for Optical Engineering, 2018)
The 5TW, 1kHz, passively CEP-stabilized ELI-ALPS SYLOS few-cycle laser system demonstrated state-of-the-art output parameters, excellent overall stability and reliability during the recently finished half-year trial period. Long-term performances were cross-checked by several different experimental methods.
CRIS-Team Scopus Importer:2023-04-20